Improving Students Speaking Ability By Using Pair-Work Method At Seventh Grade Of SMPN 08 Kabupaten Tebo - Saputra, Riyadi; Khairita, Martiyah Nurni; Amlada, Khoiri (Universitas Pahlawan Tuanku Tambusai, 2024)
Speaking skill in learning English for class VII students at SMPN 08 Tebo is still low. This research aims to improve students' English speaking skills through the pair-work method for class VII students at SMPN 08 TEBO in the 2023/2024 academic year. This research was conducted by using classroom action research which contained planning, implementing actions, observing and reflecting. The research subjects were class VII students at SMPN 08 TEBO. The class consisted of 29; 21 men and 9 women. Then the research data was through quantitative data. Quantitative data was obtained from tasks and tests. Students' speaking skills tasks scores are obtained in each cycle. Meanwhile, the test was obtained at the end of each cycle. The results of the exercises in cycles 1 to 2 show that the pair-work method can improve students' speaking skills. In the first cycle of the first meeting, the score of students who achieved the KKTP was 31%, and increased at the second meeting to 55%. Furthermore, in cycle 2, meeting 1, the student's speaking skill score was 62% and the student's speaking skill score at meeting 2 in cycle 2 rose to 83%. Then, in the test results in the first cycle, the results of the students' speaking skills were 62%. Then in the 2nd cycle 2 test it rose to 83%. It can be said that the pair-work method can be used to improve students' ability to speak English, especially for class VII students at SMPN 08 TEBO for the 2023/2024 academic year.